The Role of Cyber Law in Addressing Cybercrime in Indonesia - Junaidi Lubis; Lubis, Muhammad Koginta; Dermawan, Haris Dermawan (Alauddin Law Development Journal (ALDEV), 2025)
Cybercrime has become a real threat in today's digital age. Technological developments cannot be stopped, including legal issues. The law must also be able to anticipate that technological developments must be supervised so as not to cause new crimes in the digital world. Technological developments do not necessarily always have a bad impact on people's lives, therefore it needs to be limited for the comfort and safety of the community in the digital space so as not to take new victims. Method in this study is normative legal research and the approach carried out is a conceptual approach. The results of the study indicate that with the existence of cyber law in Indonesia, every crime that occurs in the digital world can be solved with cyber law whose function is as a legal umbrella in handling cybercrimes that befall every citizen.